Alle vegar fører til Nidaros - Myking, Synnøve Midtbø (Collegium Medievale, 2020)
This article discusses a fragment of Stephen of Tournai’s Summa in decretum Gratiani, now in the Norwegian National Archives, but originally part of a manuscript copied in France between around 1175 and 1200. The medieval provenance of the manuscript is uncertain, but the article discusses the possible ways in which it might have ended up in Norway, where it was used as binding material for seventeenth-century accounts from the area around Trondheim: was it brought to Norway as a result of contacts forged in twelfth-century Paris, or did it come to Denmark first? By showing that the manuscript, no matter whether it first came to Norway or Denmark, would have travelled thanks to the same type of contacts, involving the same type of people, the article uses the absence of a known medieval provenance as an opportunity to shed light on Danish-Norwegian connections and parallels in the High Middle Ages.